PENGARUH TERAPI MUROTTAL SURAH AR-RAHMAN IRAMA JIHARKAH TERHADAP TEKANAN DARAH PENDERITA HIPERTENSI DI UPT GADING REJO - Purwono, Janu; Sari, Rita (Coping: Community of Publishing in Nursing; Vol 11 No 5 (2023): Oktober 2023DO - 10.24843/coping.2023.v11.i05.p09, 2023)
The prevalence of hypertension sufferers in the world and Indonesia is increasing. Various factors related to genetics and lifestyle such as lack of physical activity, intake of salty and fat-rich foods as well as smoking and drinking habits play a role in soaring hypertension rates. One of the complementary therapies that can control blood pressure is murottal surah Ar-Rahman therapy. The aim of the research was to determine the effect of murottal therapy of surah Ar-Rahman with the jiharkah rhythm on changes in blood pressure in hypertension sufferers in the working area of ??the UPT Puskesmas Gading Rejo Pringsewu Lampung. Quantitative research design with a quasi-experimental method with a one group pretest and posttest design without a control group. The research population was hypertension sufferers at the UPT Puskesmas Gading Rejo in September 2023. The total sample was 70 respondents using the purposive sampling method. Analysis used a paired test on systolic blood pressure and the Wilcoxon test on diastolic blood pressure. The results of statistical tests using the paired t test showed that the p-value of systolic blood pressure before and after murottal therapy of surah Ar-Rahman was 0,002 and the results of the Wilcoxon test of diastolic blood pressure before and after murottal therapy of surah Ar-Rahman obtained a p-value is 0,000. In conclusion, there is an effect of murottal therapy of surah Ar-Rahman with jiharkah rhythm on blood pressure before and after intervention is given to hypertension sufferers, so that murottal therapy of surah Ar-Rahman with jiharkah rhythm is effective for lowering blood pressure in hypertension sufferers.